2003
DOI: 10.1177/09680519030090040701
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptor regulation of LPS-induced signaling and pathophysiology

Abstract: Macrophages express several lipopolysaccharide (LPS) binding proteins and are potently activated by LPS to produce inflammatory mediators. Recent studies have shown that receptors for exogenous nucleotides (P2X and P2Y purinergic receptors) can modulate macrophage production of TNF-alpha, IL-1beta and nitric oxide (NO) following LPS exposure. Macrophages and LPS-stimulated monocytes express elevated levels of P2Y1, P2Y2 and P2X7 mRNA, suggesting that both P2Y and P2X receptors can contribute to LPS-induced pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…A role for G proteins in LPS signaling was further bolstered by the observations that many LPS-inducible events (e.g., MAPK activation, NF-B activation, and others) are mimicked by G protein activation and that LPS increased GTPase activity in macrophages (reviewed in Ref. 60). Since the original observations of Jakway and DeFranco, there have been a number of papers that have confirmed and extended these findings in human and murine monocytes and macrophages, .…”
Section: Discussionmentioning
confidence: 99%
“…A role for G proteins in LPS signaling was further bolstered by the observations that many LPS-inducible events (e.g., MAPK activation, NF-B activation, and others) are mimicked by G protein activation and that LPS increased GTPase activity in macrophages (reviewed in Ref. 60). Since the original observations of Jakway and DeFranco, there have been a number of papers that have confirmed and extended these findings in human and murine monocytes and macrophages, .…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that P2X 7 agonists are able to modulate macrophage activation in response to LPS, resulting in increased pro-inflammatory mediator production [17,18,23,56,[67][68][69][70][71][72][73][74][75][76]. Because LPS is known to activate ROS production in leukocytes [77,78], and because P2X 7 activation is able to augment several LPSinduced signaling events, we tested the hypothesis that P2X 7 -stimulated ROS production is enhanced in LPSprimed macrophages.…”
Section: P2x 7 Activation Mediates Nadph Oxidase-dependent Ros Producmentioning
confidence: 99%
“…When properly regulated, ROS maintain an integral role in host defense, regulation of apoptosis, and modulation of cell signaling. The generation of ROS has also been implicated in several human disorders, including hypertension, atherosclerosis, ischemia/reperfusion injury, neurodegenerative disease, chronic granulomatous disease, and the deleterious effects of aging [18,56]. The use of ROS by leukocytes in the defense against pathogens is well recognized, but the role of ROS as second messengers is sill emerging, e.g., ROS generation has been linked to the activation of transcription factors, including apurinic/apyrimidinic endonuclease 1 (APE1)/Ref1, nuclear factor ÎșB (NFÎșB), and AP-1, as well as the signaling kinases p90 ribosomal S6 kinase (p90RSK) and various MAPKs [21,[57][58][59][60][61][62][63][64][65].…”
Section: P2x 7 Activation Mediates Nadph Oxidase-dependent Ros Producmentioning
confidence: 99%
See 2 more Smart Citations